Commercial real estate in Denmark - Jakob Guldbæk Mikkelsen; Emil Toft Vestergaard (Danmarks Nationalbank, 2024)
The value of the Danish commercial real estate market is large and developments within this market can have widespread implications for the financial system and the real economy. This memo provides an overview of the Danish commercial real estate market. It maps the stock of Danish commercial real estate properties by region, type of property and ownership. It also provides an overview of the business model of commercial real estate companies, focusing on the economic drivers of income and expenses and the principles underlying the valuation of commercial real estate. Lastly, it describes credit institutions' exposure to the commercial real estate sector.
Keywords: 330; Gewerbeimmobilien; Immobilienmarkt; Immobilienbewertung; Immobilienwirtschaft; Immobilienfinanzierung; Dänemark